2023
DOI: 10.1111/febs.16713
|View full text |Cite
|
Sign up to set email alerts
|

Rational engineering of AA5_2 copper radical oxidases to probe the molecular determinants governing their substrate selectivity

Abstract: Fungal copper radical oxidases (CROs) from the Auxiliary Activity family 5 (AA5) constitute a group of metalloenzymes that oxidize a wide panel of natural compounds, such as galactose-containing saccharides or primary alcohols, into product derivatives exhibiting promising biotechnological interests. Despite a well-conserved first copper-coordination sphere and overall fold, some members of the AA5_2 subfamily are incapable of oxidizing galactose and galactosides but conversely efficiently catalyse the oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
(102 reference statements)
0
0
0
Order By: Relevance
“…No substrate or product complexes of AA5 members have been solved, so direct information on active-site interactions is currently lacking ( 19 , 32 , 33 , 37 , 64 ). However, site-directed mutagenesis and in silico studies have implicated several key active site residues in the modulation of substrate specificity ( 47 , 65 67 ). Yet, these studies also indicate that substrate specificity cannot be readily attributed to the effects of any specific amino acids in a predictable manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No substrate or product complexes of AA5 members have been solved, so direct information on active-site interactions is currently lacking ( 19 , 32 , 33 , 37 , 64 ). However, site-directed mutagenesis and in silico studies have implicated several key active site residues in the modulation of substrate specificity ( 47 , 65 67 ). Yet, these studies also indicate that substrate specificity cannot be readily attributed to the effects of any specific amino acids in a predictable manner.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of one or both glutamines is generally, but not exclusively (e.g., Efe GalOx), correlated with a loss of GalOx activity. A recent study on the engineering of Cgr AlcOx has shown that these glutamines increase affinity for galactose, likely through hydrogen bonding ( 65 ). Interestingly, Xpa GalOx, which has a twofold higher catalytic efficiency and 10-fold lower K M on galactose compared to Fgr GalOx ( Table 1 ), contains an arginine at the position corresponding to Q326 in Fgr GalOx ( Table 2 ; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A variant with four (V4) and a variant with six mutations (V6) was identified, showing a comparable affinity to Dgalactose like the FgrGOx. [40] However, the variants had a 10fold lower activity towards aliphatic or aromatic alcohols. Both studies demonstrate that only a few amino acids are needed to manipulate the substrate spectrum of CROs, allowing rational engineering to change significantly the substrate preference.…”
Section: Functionalisation Of Sugarsmentioning
confidence: 98%
“…Using structure‐based rational engineering, 21 Cgr AAO variants were generated with mutations in six residues (W39F, F138W, M173R, F174Y, T246Q and L302P) responsible for substrate recognition at the active site, Figure 3b. A variant with four (V4) and a variant with six mutations (V6) was identified, showing a comparable affinity to D‐galactose like the Fgr GOx [40] . However, the variants had a 10‐fold lower activity towards aliphatic or aromatic alcohols.…”
Section: Introductionmentioning
confidence: 99%